Factors Influencing Hand Washing With Soap Compliance Level Among Beach Tourism Workers - Musfirah Musfirah; Ahmad Faizal Rangkuti; Fenni Nurul Khotimah (International Journal of Public Health Science (IJPHS), 2022)
The compliance level of beach tourism workers is the most important factor to prevent COVID-19 spread in tourism destinations. The availability of hand washing facilities and COVID-19 health protocol media can influence beach tourism workers' compliance with Hand Washing With  Soap (HWWS). The study aimed to determine  the related factors toward HWWS compliance level among beach tourism workers. A cross-setional study involved 60 beach tourism workers using total sampling technique from September 2021 to November 2021. Questionnaires were used to assess the  availability of hand washing facilities, health protocol media, and HWWS compliance levels in beach tourism workers. The descriptive and fisher’s tests are used in the analysis. The finding study demonstrates that majority of respondents "support" the availability of hand washing facilities, the COVID-19 health protocols media, and had a good HWWS compliance among beach tourism workers. We concluded that the availability of hand washing facilities as main factor with related to HWWS compliance level among beach tourism workers.Keywords : COVID-19, Compliance level, Beach  tourism workers, Facilities, Hand washing